Treatment Guidelines for Patients with Schizophrenia or Psychotic Disorder who are Hospitalized in a Psychiatry Clinic - Alptekin, Koksal; Ucok, Alp; Ayer, Ahmet; Unal, Ahmet; Erol, Atila; Ensari, Hulya; Ozguven, Halise Devrimci (Kure Iletisim Grubu A S, 2014)
In schizophrenia, hospitalization is generally indicated for patients who pose a serious threat to themselves or others, those who are disorganized to the extent of not to being able to look after themselves or who are experiencing delusions/hallucinations. The steps to be taken during the time hospitalization of patients with schizophrenia and psychosis as determined by the Hospital Setting Expert Committee (HSEC), consisting of 19 psychiatrists from Europe, who are specialists in the acute management of schizophrenia patients, have been arranged under 7 topics in the form of algorithms (Algorithm 1- Assessing the acute psychotic episode; Algorithm 2- Defining treatment targets for inpatient treatment; Algorithm 3- Emergency management; Algorithm 4- Defining treatment targets during inpatient treatment; Algorithm 5- Pharmacological treatment at the time of hospitalization; Algorithm 6-Non-pharmacological treatment during inpatient treatment; Algorithm 7- Improvement of well-being. The Turkish version of this guideline, which was revised to meet the conditions in our country, was used and tested in eight psychiatry clinics. Following these algorithms for hospitalized schizophrenia patients may be helpful for doctors in managing the patients and facilitating their participation in social life.
Psikiyatri kliniğine yatırılan şizofreni ve psikotik bozukluğu olan hastaların tedavi rehberi
Keywords: schizophrenia; treatment; algorithm; hospital treatment; treatment guideline